THE EFFECT OF PRINCIPAL SUPERVISION AND BURNOUT ON TEACHER WORK ETHICS AT RITA KAKA PUBLIC ELEMENTARY SCHOOL - Umar Ali; Ezra Tari; Hendrik A.E. Lao; Lanny I.D. Koroh (Afeksi: Jurnal Penelitian dan Evaluasi Pendidikan, 2023)
This research begins with the author's anxiety about the decline in the teacher's work ethic. Many factors affect the decline in work ethic. One of them is Burnout. Due to poor collaboration between superiors and subordinates, teacher incompetence is increasing, and teacher interruption rates are high. This is reflected in the work ethic of SD Negeri Rita-Kaka teachers. The teacher's work ethic still needs to be revised. The type of quantitative research used is descriptive regression, characterized by analyzing interactions between endogenous variables consisting of central school control, teacher burnout, and work ethic as exogenous variables. Regarding the impact of the principal's leadership and Burnout on the morale of SD Rita-Kaka Elementary teachers, it was found that, first, the contribution of the principal's leadership to teacher morale was less impressive. Second, Burnout's contribution to teacher morale is quite impressive. Third, the principal's supervision and burnout contribution are very influential.